EFFECTIVENESS OF MAJAPAHIT LEAF EXTRACT (Crescentia cujete L.) AS A NATURAL PESTICIDE FOR BANANA LEAF ROLLER CATERPILLAR (Erionota thrax L). - Pratomo, Ibnu; Aminatun, Tien; Kuswandi, Paramita Cahyaningrum (Indonesian Journal of Bioscience (IJOBI), 2023)
This study aims to determine the effectiveness of Majapahit leaf extract (Crescentia cujete L.) on the feeding activity and mortality of the banana leaf roller caterpillar (Erionota thrax L.), and also the optimal concentration that affects the feeding activity and mortality of the banana leaf roller caterpillar (Erionota thrax L.). This research is a completely randomized design (CRD) experiment with 4 treatments and 3 replicates. In thos study, 60 third instar larvae of Erionota thrax L. were taken using the transect method from several villages in Purworejo district, Central Java. The pesticide from Majapahit leaves was made through a simple extraction method with 4 concentrations: 0%, 25%, 30% and 35%. The results showed that Majapahit leaf extract had an effect on feeding activity and mortality of the banana leaf rolling caterpillar. The optimal concentration of Majapahit leaf extract that affects feeding activity and pest mortality was 35%.